Pengaruh Kinerja Keuangan dan Ukuran Perusahaan Terhadap Cash Holding Perusahaan - Dewi, Reni Sartika; Walkomaroh, Manju; Mulyana, Jaka; Nofryanti, Nofryanti (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2023)
This research aims to analyze and obtain empirical evidence of the influence of financial performance and company size on company cash holdings. Empirical studies on banking sector companies listed on the Indonesian Stock Exchange in 2018 - 2022. This research is quantitative research with descriptive methods, the data used is secondary data in the form of financial reports which contain figures which are then tested and describe or provide an overview of the results. The sample selection in this research used a purposive sampling technique. The data analysis method used is panel data regression processed using Eviews version 9. The population used in this research is banking sector companies listed on the Indonesia Stock Exchange in 2018-2022, totaling 41 companies. The sample obtained was 37 companies with 5 years of research, the total research data obtained was 185. The results of this research show that financial performance as measured by ROA and DAR has no influence on cash holding, while company size has an influence on company cash holdings. Together, the variables financial performance and company size have an influence on the company's cash holding.Keywords: Financial Performance, Company Size, Cash Holding